The civil engineering in the conservation and restoration of heritage buildings and monuments (Revista de Diavulgación L'esprit Ingénieux, 2021)
The conservation of heritage buildings is the preservation of the monuments that represent and immortalize a cultural memory, however it’s always related to architectonical procedures, by this reason, the civil engineering processes, behind the architectonical interventions, that guarantee the stability and safety of these buildings do not have enough visibility so that engineers get interested in this work, therefore, the work is to explain the importance of civil engineering in the preservation of heritage buildings.
Keywords: Culture; conservation; engineering; heritage